The effects of energy taxes level on greenhouse gas emissions in the environmental policy measures framework - Firtescu, Bogdan Narcis; Brinza, Florin; Grosu, Maria; Doaca, Erika Maria; Siriteanu, Adelina Andreea (Frontiers in Environmental Science, 2023)
In the last decades, all countries have pursued an ambitious climate policy, thus showing a growing concern about climate change, global warming, greenhouse gas (GHG) emissions, or environmental taxes. Water, air, and soil pollution caused by gas emissions directly affect human health, but also the economies of states. As people's ability to adapt to novel changes becomes increasingly difficult, globally, they are constantly trying to reduce their greenhouse gas (GHG) emissions in a variety of ways. Environmental taxes, in general, and energy taxes, in particular, are considered effective tools, being recommended by specialists, among other instruments used in environmental policy. The aim of this research is to assess, empirically, the influence of the environmental taxes levels on greenhouse gas (GHG) emissions in 28 European countries, with a time span between 1995 and 2019. Regarding the empirical research, the proposed method is related to dynamic common-correlated eﬀects model with heterogeneous coeﬃcients over cross-sectional units and time periods. The results obtained show that the increase in environmental taxes generates a decrease in greenhouse gas (GHG) emissions. To test the robustness of our results, we have added in the model supplementary economic and social control variables, such gross domestic product (GDP), population density, exports, or imports. Overall, our paper focuses on the role of environmental policy decisions on greenhouse gas (GHG) emissions, the results of the study showing a close link between the taxation level and the reduction of gas emissions.